2014
DOI: 10.1097/qai.0000000000000185
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From a Review of Interventions for Adolescent and Young Key Populations in Asia Pacific and Opportunities for Programming

Abstract: Although structural factors play a key role in access and uptake of HIV prevention services for adolescent and YKP, further qualitative research is needed to understand and mitigate the drivers of vulnerability and constructed perceptions of risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
(49 reference statements)
1
19
0
Order By: Relevance
“…Unprotected sex is an important risk factor for negative health outcomes among young people, accounting for 4% of disability-adjusted life years (DALYs) in those aged 10–24 [ 12 ]. Several studies have shown younger age is associated with more frequent unprotected sex among KP [ 13 ], often due to lower levels of education, knowledge, and risk perception [ 13 15 ]. Young key populations (YKP) may also be unaware of where to access condoms and other contraception.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unprotected sex is an important risk factor for negative health outcomes among young people, accounting for 4% of disability-adjusted life years (DALYs) in those aged 10–24 [ 12 ]. Several studies have shown younger age is associated with more frequent unprotected sex among KP [ 13 ], often due to lower levels of education, knowledge, and risk perception [ 13 15 ]. Young key populations (YKP) may also be unaware of where to access condoms and other contraception.…”
Section: Resultsmentioning
confidence: 99%
“…In one study of young MSM aged 16–20, considering a relationship to be serious was associated with an eight-fold increase in the rate of unprotected sex [ 24 ]. For TG women, condom negotiation may be more difficult given their female gender identity and socially constructed role, and young TG people may be more likely to have unprotected sex to validate their gender identity [ 13 ]. Among young PWID, low rates of condom use are often associated with other high-risk practices such as needle sharing or smoking drugs together [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding may reflect that youth are vulnerable to STIs, possibility due to lower levels of education, risk perception, and the higher prevalence of risky sexual behaviors (23,24). Because HIV transmission among youth MSM in China has become a rapidly emerging public health problem (25,26), interventions including education on safer sexual behaviors, improving the coverage and pertinence voluntary counseling, and testing work and STI treatments are imperative to prevent STIs infections in MSM.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 2.1 million adolescents (11-19 years) who are infected with HIV, about 1.3 million (62%) live in Eastern and Southern Africa [6,7]. It is estimated that 95% of new infections among adolescents in Asia are among key populations such as people who inject drugs (PWID), men having sex with men (MSM) and sex workers [8] and 70% of all individuals who inject drugs are under the age of 25 [9]. This can be supported by empirical evidence that key populations and their sexual partners account for a high proportion of new HIV infections in countries such as Dominican Republic 47%, Kenya 33%, Morocco 80%, Mozambique 27.5%, Nigeria 51%, Peru 65% [10].…”
Section: Introductionmentioning
confidence: 99%